A SiC nano whisker reinforced silicon carbide ceramic and preparation method thereof
By generating SiC nanowhiskers in situ in silicon carbide ceramic materials, using the stress loss mechanism, the problem of excessive brittleness of reactive sintered silicon carbide ceramic materials is solved, and the toughening and performance improvement of the material is achieved.
Patent Information
- Application Number
- CN202411968641.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
The brittleness of the reactive sintered silicon carbide ceramic material is too high, has low toughness, and is prone to brittle fracture, affecting the performance of the material.
By generating SiC nanowhiskers in situ inside the material, the stress loss mechanism is used to enhance the toughness of the ceramic material. The specific method includes producing SiC nanowhiskers with silicon carbide powder, carbon black and silica powder as the main raw materials, and through two steps of carbon thermal reduction and reaction seepage.
The toughening of the reactive sintered silicon carbide ceramics is achieved, which improves the use performance of the material, and simplifies the process, which is suitable for large-scale promotion.
Smart Images

Figure CN119775038A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of silicon carbide ceramic preparation, and in particular relates to a SiC nano whisker reinforced silicon carbide ceramic and a preparation method thereof. Background Art
[0002] Silicon carbide ceramic materials have good mechanical properties such as high hardness, high stiffness, and wear resistance. At the same time, they have excellent thermal properties such as anti-oxidation, thermal shock resistance, high thermal conductivity, and low thermal expansion coefficient, which makes them applicable to precision bearings, compression cylinders, wear-resistant seals, gas rotors, nozzle nuclear reactors, and thermonuclear reactors. The mainstream processes for preparing silicon carbide ceramics include pressureless sintering, hot pressing sintering, and reaction sintering; among them, hot pressing sintering mainly applies pressure to the green body during the sintering process to accelerate densification. Reaction sintering generally allows the raw material mixture to undergo a solid-phase reaction to synthesize ceramic materials; relatively speaking, its preparation process is simple, and the sintering temperature is low, the sintering time is short, and net size sintering can be achieved, etc., and it has broad application prospects.
[0003] Reaction-sintered silicon carbide ceramics are made by traditional reaction sintering methods. This material can be used in aerospace, high-temperature structural parts, wear-resistant components and other fields. However, the application of reaction-sintered silicon carbide ceramics is mainly limited by: its brittleness is too large, its toughness is low, and it is easy to cause brittle fracture during application, resulting in material damage. At present, the solution to this problem usually includes: introducing nano whiskers or fibers into reaction-sintered silicon carbide ceramics to toughen them, and through mechanisms such as fiber breakage, fiber debonding, fiber pull-out, crack bridging and crack deflection, the energy loss of the internal stress of the ceramic material is achieved to improve the material toughness.
[0004] However, some externally added whisker reinforcements are difficult to disperse and have composition differences with ceramic materials, which can form defects inside the material and affect the material's performance. Summary of the invention
[0005] In view of this, the present invention provides a SiC nanowhisker reinforced silicon carbide ceramic and a preparation method thereof. The preparation method of the present invention can generate nanowhiskers in situ, and can achieve toughening of reaction-sintered silicon carbide ceramics through a stress loss mechanism inside the material. At the same time, the process can be simplified, and the process is suitable for large-scale promotion and application.
[0006] The present invention provides a method for preparing SiC nano whisker reinforced silicon carbide ceramics, comprising:
[0007] Step S1, using 35-55wt% of silicon carbide powder, 30-45wt% of carbon black and 10-20wt% of silicon dioxide powder as main raw materials, mixing with a binder, a dispersant and water, wherein the amount of the binder and the dispersant is 1-5wt% of the total weight of the main raw materials respectively, to prepare a ceramic slurry;
[0008] Step S2, placing the ceramic slurry in a mold, allowing it to stand and dry to form, and demolding to obtain a porous ceramic body;
[0009] Step S3: bury the porous ceramic body with silicon powder, raise the temperature to 1450-1550° C. in a flowing argon atmosphere, and perform carbon thermal reduction while maintaining the temperature to obtain SiC nw / SiC / C porous ceramic preform; then heating to 1650-1750°C, vacuum insulation at a vacuum degree of 1-30Pa, and then cooling to obtain SiC nano whisker reinforced silicon carbide ceramics.
[0010] In an embodiment of the present invention, in step S1, the purity of the silicon dioxide powder is 90-99.9% and the particle size is 1-10 μm.
[0011] In an embodiment of the present invention, in step S1, the purity of the silicon carbide powder is 85-99.9%, and the particle size is 5-40 μm; the purity of the carbon black is 95-99.9%, and the particle size is 1-20 μm.
[0012] In an embodiment of the present invention, in step S1, the binder is one or more of hydroxymethyl cellulose salt and hydroxyethyl cellulose; and / or the dispersant is one or more of ethanol, methylpentanol, polyethylene glycol and fatty acid polyethylene glycol ester.
[0013] In an embodiment of the present invention, in step S1, silicon carbide powder, silicon dioxide powder and carbon black are first mixed and ball-milled for 2-4 hours according to a certain proportion, and then a binder, a dispersant and water are added to prepare a ceramic slurry.
[0014] In an embodiment of the present invention, step S2 comprises: injecting the ceramic slurry into a mold, leaving it to stand for 7 to 9 hours, freeze-drying or forced air drying it for 24 hours, and then demolding it to obtain a porous ceramic body.
[0015] In an embodiment of the present invention, in step S3, the amount of silicon powder used is twice the weight of the porous ceramic body, and the silicon powder is evenly spread and buried in two times.
[0016] In an embodiment of the present invention, in step S3, the heat preservation time under the argon atmosphere is 2 to 10 hours, the vacuum heat preservation time is 30 to 120 minutes, and then naturally cooled to obtain SiC nano whisker reinforced silicon carbide ceramics. Further, in step S3, the heat preservation time under the argon atmosphere is 2 to 5 hours; the vacuum degree of the vacuum heat preservation is 5 to 30Pa.
[0017] The present invention provides a SiC nano whisker reinforced silicon carbide ceramic made by the above-mentioned preparation method.
[0018] Compared with the prior art, the present invention uses a certain proportion of silicon carbide powder, carbon black and silicon dioxide powder as main raw materials, and generates SiC ceramic nano whiskers in situ in a porous ceramic body through carbon thermal reduction of silicon dioxide powder and carbon black; and reacts molten Si with carbon black to generate SiC through reactive infiltration to achieve reactive sintering of ceramic materials. The excess carbon black in the present invention can ensure the complete reaction of silicon dioxide, and as a carbon source for reactive infiltration, a one-step method combining carbon thermal reduction and reactive infiltration is used to obtain SiC nano whisker reinforced silicon carbide ceramics. The present invention utilizes the in-situ generation of SiC nano whiskers of the same composition, and the stress loss mechanism inside the SiC ceramic material achieves toughening of reactive sintered silicon carbide ceramics. The present invention improves the preparation efficiency of the material, has a simple process, and is easy to control, which is conducive to large-scale promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention or the core of the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings under the premise of continuous creative work.
[0020] Figure 1 To explore SiC prepared by carbothermal reduction before the implementation of the present invention nw / SiC / C composite porous ceramics XRD pattern;
[0021] Figure 2 To explore SiC prepared by carbothermal reduction before the implementation of the present invention nw / SiC / C composite porous ceramics SEM image. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. Unless otherwise defined, all professional terms used hereinafter have the same meaning as those skilled in the art generally understand. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0023] The present invention provides a method for preparing SiC nano whisker reinforced silicon carbide ceramics, comprising:
[0024] Step S1, using 35-55wt% of silicon carbide powder, 30-45wt% of carbon black and 10-20wt% of silicon dioxide powder as main raw materials, mixing with a binder, a dispersant and water, wherein the amount of the binder and the dispersant is 1-5wt% of the total weight of the main raw materials respectively, to prepare a ceramic slurry;
[0025] Step S2, placing the ceramic slurry in a mold, allowing it to stand and dry to form, and demolding to obtain a porous ceramic body;
[0026] Step S3: bury the porous ceramic body with silicon powder, raise the temperature to 1450-1550° C. in a flowing argon atmosphere, and perform carbon thermal reduction while maintaining the temperature to obtain SiC nw / SiC / C porous ceramic preform; then heating to 1650-1750°C, vacuum insulation at a vacuum degree of 1-30Pa, and then cooling to obtain SiC nano whisker reinforced silicon carbide ceramics.
[0027] The invention can prepare the enhanced reaction sintered silicon carbide ceramic material with good performance, and the method is simple and easy to implement, and has high preparation efficiency.
[0028] In a specific embodiment of the present invention, the main raw materials of silicon carbide powder, silicon dioxide powder and carbon black are mixed and ball-milled according to a certain weight ratio for 2-4 hours; after the raw materials are fully mixed, a binder, a dispersant and water are added to prepare a ceramic slurry.
[0029] The weight proportion of the main raw materials is as follows: silicon carbide powder 35-55wt%, preferably 45-50wt%; carbon black 30-45wt%, preferably 35-40wt%; silicon dioxide powder 10-20wt%, preferably 10-15wt%. The main raw materials described in the embodiments of the present invention can all be commercially available, and the purity of the silicon dioxide powder is preferably 90-99.9%, and the particle size is 1-10μm. The purity of the silicon carbide powder can be 85-99.9%, and the particle size is 5-40μm. The purity of the carbon black can be 95-99.9%, and the particle size is 1-20μm.
[0030] In the embodiment of the present invention, the ball-milled raw material can be placed in a stirring tank, 1 to 5 wt% of the total weight of the main raw material binder and 1 to 5 wt% of the total weight of the main raw material dispersant are added, and then 80 to 100 wt% of water of the total weight of the main raw material is added thereto, and stirring is continued for 30 to 60 minutes. The binder is preferably one or more of hydroxymethyl cellulose salt and hydroxyethyl cellulose, more preferably sodium carboxymethyl cellulose and / or hydroxyethyl cellulose. The dispersant is preferably one or more of ethanol, methyl pentanol, polyethylene glycol and fatty acid polyethylene glycol ester, more preferably ethanol, methyl pentanol or polyethylene glycol. Among them, the laboratory usually uses deionized water to prepare the slurry, and the binder and dispersant involved are additives well known to those skilled in the art.
[0031] After the ceramic slurry is prepared, it is poured into a mold in the embodiment of the present invention, preferably left to stand for 8 hours, and then freeze-dried or air-dried for 24 hours before demolding to obtain a porous ceramic body. The mold structure and drying method are well known to those skilled in the art and are not particularly limited in the present invention.
[0032] In the embodiment of the present invention, silicon powder of the same weight as the porous ceramic body is weighed and poured into a graphite crucible and spread, the porous ceramic body is placed on the spread silicon powder, and then the silicon powder of the same weight is weighed and spread on the porous ceramic body, so that the porous ceramic body is buried in the silicon powder; the graphite crucible can be placed in a vacuum carbon tube furnace, the air inlet valve and the exhaust valve are opened, and the temperature is raised to 1450-1550°C under a flowing argon atmosphere, and carbon thermal reduction is performed by heat preservation to form a SiC nanowhisker / SiC / C porous ceramic preform. Preferably, the heat preservation time under the argon atmosphere is 2-10 hours, and further 2-5 hours. In addition, there are no special restrictions on the parameters of the silicon powder and flowing argon gas involved.
[0033] After the insulation is completed, the specific embodiment of the present invention closes the air inlet valve and the exhaust valve, opens the vacuum valve and the vacuum pump, maintains the vacuum degree in the carbon tube furnace at 1 to 30 Pa, preferably 5 to 30 Pa, raises the temperature to 1650 to 1750° C. for vacuum reaction infiltration, and performs vacuum insulation for 30 to 120 minutes. After the insulation is completed, the furnace is naturally cooled to obtain a reaction-sintered silicon carbide ceramic material reinforced with SiC nano whiskers, referred to as SiC nano whisker reinforced silicon carbide ceramic.
[0034] Accordingly, the embodiment of the present invention provides a SiC nano whisker reinforced silicon carbide ceramic prepared by the preparation method as described above. It is a reaction-sintered silicon carbide ceramic reinforced with SiC nano whiskers, and the in-situ generated SiC nano whiskers achieve toughening of the reaction-sintered silicon carbide ceramic through a stress loss mechanism inside the material, and the material has good performance.
[0035] The embodiment of the present invention obtains a SiC nano whisker reinforced reaction sintered silicon carbide ceramic material through a one-step method combining a carbothermal reduction method and a reactive infiltration method, thereby improving the preparation efficiency of the material.
[0036] In order to better understand the present invention, the content of the present invention is further explained in conjunction with the following examples, but the content of the present invention is not limited to the following examples. Unless otherwise specified, the various reagents and raw materials used in the present invention are all commercially available products or products that can be prepared by recognized methods, and the material sample testing is carried out according to the national standard method.
[0037] Example 1
[0038] The steps of SiC nano whisker reinforced reaction sintered silicon carbide ceramic and preparation method thereof include:
[0039] Step 1: Use 50wt% of silicon carbide powder, 35wt% of carbon black and 15wt% of silica powder as the main raw materials, ball-mill the SiC powder, silica powder and carbon black for 3 hours to make them fully mixed, put the ball-milled raw materials into a stirring tank, add 5wt% of the total weight of the main raw materials, and 5wt% of the total weight of the main raw materials. Dispersant, then add 100% of the total weight of the main raw materials. Deionized water, stirring continuously for 30 minutes, obtain a ceramic slurry.
[0040] Step 2: pour the ceramic slurry into a mold, let it stand for 8 hours, freeze-dry or blow dry it for 24 hours, and demold to obtain a porous ceramic body.
[0041] Step 3: Weigh the same weight of silicon powder as the porous ceramic body, pour it into a graphite crucible and spread it, place the porous ceramic body on the spread silicon powder, and then weigh the same weight of silicon powder and spread it on the porous ceramic body so that the porous ceramic body is buried in the silicon powder. Put the graphite crucible into a vacuum carbon tube furnace, open the air inlet valve and the exhaust valve, heat it to 1500°C in a flowing argon atmosphere, keep it warm for 2 hours, and obtain SiC by carbon thermal reduction. nw / SiC / C porous ceramic preform;
[0042] Step 4: After the insulation is completed, close the air inlet valve and the exhaust valve, open the vacuum valve and the vacuum pump, maintain the vacuum degree in the carbon tube furnace at 5Pa, heat to 1650°C, and keep warm for 30 minutes. After the insulation is completed, cool naturally to obtain SiC nanowhisker reinforced reaction sintered silicon carbide ceramic material.
[0043] The purity of the silicon carbide powder is 95% and the particle size is 5 μm; the purity of the silicon dioxide powder is 99% and the particle size is 5 μm; the purity of the carbon black is 98% and the particle size is 15 μm. The binder is sodium hydroxymethyl cellulose and the dispersant is polyethylene glycol.
[0044] The flexural strength of the SiC nanowhisker reinforced reaction sintered silicon carbide ceramics is 352MPa and the fracture toughness is 4.3MPa·m 1 / 2 .
[0045] Figure 1 Before the implementation of the present invention, SiC prepared by carbon thermal reduction at 1400°C was explored. nw From the XRD (X-ray diffraction) diagram of / SiC / C composite porous ceramics, it is found that silicon dioxide is converted into SiC and a small amount of C remains, which can be used as a carbon source for vacuum reactive infiltration. Figure 2 Before the implementation of the present invention, SiC prepared by carbon thermal reduction at 1400°C was explored. nw / SiC / C composite porous ceramic SEM (scanning electron microscope) image, analysis shows that SiC whiskers are formed in the porous ceramic preform, and have no effect on the SiC and C grains and the pore distribution of the porous ceramic, and the subsequent vacuum reactive infiltration treatment can be carried out normally.
[0046] Example 2
[0047] The method is consistent with that of Example 1, except that the carbon thermal reduction temperature is 1450°C.
[0048] The flexural strength of the SiC nanowhisker reinforced reaction sintered silicon carbide ceramics is 346MPa and the fracture toughness is 4.1MPa·m 1 / 2 .
[0049] Example 3
[0050] The method is consistent with that of Example 1, except that the vacuum reaction infiltration temperature is 1700°C.
[0051] The flexural strength of the SiC nanowhisker reinforced reaction sintered silicon carbide ceramics is 338MPa and the fracture toughness is 4.5MPa·m 1 / 2 .
[0052] Example 4
[0053] Step 1: Use 50wt% of silicon carbide powder, 40wt% of carbon black and 10wt% of silica powder as the main raw materials, ball-mill the SiC powder, silica powder and carbon black for 3 hours to make them fully mixed, put the ball-milled raw materials into a stirring tank, add 3wt% of the total weight of the main raw materials as a binder and 3wt% of the total weight of the main raw materials as a dispersant, then add 90% of the total weight of the main raw materials as deionized water, continue stirring for 45 minutes, and obtain a ceramic slurry.
[0054] Step 2: pour the ceramic slurry into a mold, let it stand for 8 hours, freeze-dry or blow dry it for 24 hours, and demold to obtain a porous ceramic body.
[0055] Step 3: Weigh the same weight of silicon powder as the porous ceramic body, pour it into a graphite crucible and spread it, place the porous ceramic body on the spread silicon powder, and then weigh the same weight of silicon powder and spread it on the porous ceramic body so that the porous ceramic body is buried in the silicon powder. Put the graphite crucible into a vacuum carbon tube furnace, open the air inlet valve and the exhaust valve, heat it to 1550°C in a flowing argon atmosphere, keep it warm for 3 hours, and obtain SiC by carbon thermal reduction. nw / SiC / C porous ceramic preform;
[0056] Step 4: After the insulation is completed, close the air inlet valve and the exhaust valve, open the vacuum valve and the vacuum pump, maintain the vacuum degree in the carbon tube furnace at 30Pa, heat to 1750°C, and keep warm for 120 minutes. After the insulation is completed, cool naturally to obtain SiC nanowhisker reinforced reaction sintered silicon carbide ceramic material.
[0057] The purity of the silicon carbide powder is 99% and the particle size is 40 μm; the purity of the silicon dioxide powder is 96% and the particle size is 3 μm; the purity of the carbon black is 99% and the particle size is 20 μm. The binder is hydroxyethyl cellulose and the dispersant is methyl amyl alcohol.
[0058] The flexural strength of the SiC nanowhisker reinforced reaction sintered silicon carbide ceramics is 348MPa and the fracture toughness is 4.1MPa·m 1 / 2 .
[0059] Example 5
[0060] The method is consistent with that of Example 4, the only difference being that the carbon thermal reduction temperature is 1450°C.
[0061] The flexural strength of the SiC nanowhisker reinforced reaction sintered silicon carbide ceramics is 352MPa and the fracture toughness is 4.0MPa·m 1 / 2 .
[0062] Example 6
[0063] The method is consistent with that of Example 4, except that the carbon thermal reduction temperature is 1500°C.
[0064] The flexural strength of the SiC nanowhisker reinforced reaction sintered silicon carbide ceramics is 343MPa and the fracture toughness is 4.7MPa·m 1 / 2 .
[0065] Example 7
[0066] Step 1: Use 45wt% of silicon carbide powder, 40wt% of carbon black and 15wt% of silica powder as the main raw materials, ball-mill the SiC powder, silica powder and carbon black for 3 hours to make them fully mixed, put the ball-milled raw materials into a stirring tank, add 1wt% of the total weight of the main raw materials, and 1wt% of the total weight of the main raw materials. Dispersant, then add 100% of the total weight of the main raw materials. Deionized water, stirring continuously for 60 minutes, obtain a ceramic slurry.
[0067] Step 2: pour the ceramic slurry into a mold, let it stand for 8 hours, freeze-dry or blow dry it for 24 hours, and demold to obtain a porous ceramic body.
[0068] Step 3: Weigh the same weight of silicon powder as the porous ceramic body, pour it into a graphite crucible and spread it, place the porous ceramic body on the spread silicon powder, and then weigh the same weight of silicon powder and spread it on the porous ceramic body so that the porous ceramic body is buried in the silicon powder. Put the graphite crucible into a vacuum carbon tube furnace, open the air inlet valve and the exhaust valve, heat it to 1500°C in a flowing argon atmosphere, keep it warm for 4 hours, and obtain SiC by carbon thermal reduction. nw / SiC / C porous ceramic preform;
[0069] Step 4: After the insulation is completed, close the air inlet valve and the exhaust valve, open the vacuum valve and the vacuum pump, maintain the vacuum degree in the carbon tube furnace at 10Pa, heat up to 1650°C, and keep warm for 30 minutes. After the insulation is completed, cool naturally to obtain SiC nanowhisker reinforced reaction sintered silicon carbide ceramic material.
[0070] The purity of the silicon carbide powder is 97% and the particle size is 20 μm; the purity of the silicon dioxide powder is 98% and the particle size is 4 μm; the purity of the carbon black is 99% and the particle size is 10 μm. The binder is hydroxyethyl cellulose and the dispersant is ethanol.
[0071] The flexural strength of the SiC nanowhisker reinforced reaction sintered silicon carbide ceramics is 372MPa and the fracture toughness is 4.8MPa·m 1 / 2 .
[0072] Example 8
[0073] The method is consistent with that of Example 7, the only difference being that the vacuum reaction infiltration temperature is 1700°C.
[0074] The flexural strength of the SiC nanowhisker reinforced reaction sintered silicon carbide ceramics is 366MPa and the fracture toughness is 4.5MPa·m 1 / 2 .
[0075] Example 9
[0076] The method is consistent with that of Example 7, the only difference being that the vacuum reaction infiltration temperature is 1750°C.
[0077] The flexural strength of the SiC nanowhisker reinforced reaction sintered silicon carbide ceramics is 378MPa and the fracture toughness is 4.7MPa·m 1 / 2 .
[0078] As can be seen from the above examples, the embodiments of the present invention all prepare SiC whisker-reinforced reaction-sintered silicon carbide ceramics through a one-step method of carbothermal reduction and reaction infiltration, wherein the stress loss mechanism of the in-situ generated SiC nano whiskers inside the material achieves toughening of the reaction-sintered silicon carbide ceramics. At the same time, the process of the present invention is simple and the process is easy to control, which is conducive to industrial promotion.
[0079] It should be noted that, for those skilled in the art, several improvements and modifications may be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. A method for preparing SiC nanowhisker reinforced silicon carbide ceramics, characterized in that: include: Step S1, using 35-55wt% of silicon carbide powder, 30-45wt% of carbon black and 10-20wt% of silicon dioxide powder as main raw materials, mixing with a binder, a dispersant and water, wherein the amount of the binder and the dispersant is 1-5wt% of the total weight of the main raw materials respectively, to prepare a ceramic slurry; Step S2, placing the ceramic slurry in a mold, allowing it to stand and dry to form, and demolding to obtain a porous ceramic body; Step S3: bury the porous ceramic body with silicon powder, raise the temperature to 1450-1550° C. in a flowing argon atmosphere, and perform carbon thermal reduction while maintaining the temperature to obtain SiC nw / SiC / C porous ceramic preform; then heating to 1650-1750°C, vacuum insulation at a vacuum degree of 1-30Pa, and then cooling to obtain SiC nano whisker reinforced silicon carbide ceramics.
2. The method for preparing SiC nano whisker reinforced silicon carbide ceramics according to claim 1, characterized in that: In step S1, the purity of the silicon dioxide powder is 90-99.9% and the particle size is 1-10 μm.
3. The method for preparing SiC nano whisker reinforced silicon carbide ceramics according to claim 1, characterized in that: In step S1, the purity of the silicon carbide powder is 85-99.9%, and the particle size is 5-40 μm; the purity of the carbon black is 95-99.9%, and the particle size is 1-20 μm.
4. The method for preparing SiC nano whisker reinforced silicon carbide ceramics according to claim 1, characterized in that: In step S1, the binder is one or more of hydroxymethyl cellulose salt and hydroxyethyl cellulose; and / or the dispersant is one or more of ethanol, methylpentanol, polyethylene glycol and fatty acid polyethylene glycol ester.
5. The method for preparing SiC nanowhisker reinforced silicon carbide ceramics according to any one of claims 1 to 4, characterized in that: In step S1, silicon carbide powder, silicon dioxide powder and carbon black are first mixed and ball-milled for 2-4 hours according to a certain proportion, and then a binder, a dispersant and water are added to prepare a ceramic slurry.
6. The method for preparing SiC nanowhisker reinforced silicon carbide ceramics according to any one of claims 1 to 4, characterized in that: Step S2 comprises: injecting the ceramic slurry into a mold, leaving it to stand for 7 to 9 hours, freeze-drying or blast-drying it for 24 hours, and demolding it to obtain a porous ceramic body.
7. The method for preparing SiC nanowhisker reinforced silicon carbide ceramics according to any one of claims 1 to 4, characterized in that: In step S3, the amount of silicon powder used is twice the weight of the porous ceramic body, and the silicon powder is evenly spread and buried in two times.
8. The method for preparing SiC nano whisker reinforced silicon carbide ceramics according to claim 7, characterized in that: In step S3, the heat preservation time in the argon atmosphere is 2 to 10 hours, and the vacuum heat preservation time is 30 to 120 minutes, followed by natural cooling to obtain SiC nano whisker reinforced silicon carbide ceramics.
9. The method for preparing SiC nano whisker reinforced silicon carbide ceramics according to claim 8, characterized in that: In step S3, the insulation time under the argon atmosphere is 2 to 5 hours; the vacuum degree of the vacuum insulation is 5 to 30 Pa.
10. A SiC nano whisker reinforced silicon carbide ceramic prepared by the preparation method according to any one of claims 1 to 9.